Direct water-phase synthesis of lead sulfide quantum dots encapsulated by β-lactoglobulin for in vivo second near infrared window imaging with reduced toxicity. Issue 21 (18th February 2016) - Chen, Jun; Kong, Yifei; Wang, Wei; Fang, Hongwei; Wo, Yan; Zhou, Dejian; Wu, Ziying; Li, Yunxia; Chen, Shiyi
Abstract : LG capped PbS quantum dots: a highly water-dispersible and biocompatible image reporter in the second near-infrared window. Abstract : Compared to conventional fluorescence imaging in the visible (400–700 nm) and NIR-I regions (700–900 nm), optical fluorescence imaging in the second near infrared window (NIR-II, 1000–1400 nm) offers reduced photon scattering, deeper tissue penetration and lower auto-fluorescence. Despite excellent imaging capabilities, current NIR-II probes have not yet reached their full potential due to weak quantum yield, low water solubility and suboptimal biocompatibility. To address these problems, we report herein a new NIR-II fluorescent PbS quantum dots (QDs) that are fabricated in water using β-lactoglobulin (LG) as a biological template. The LG-PbS QDs exhibit satisfactory dispersibility, relatively high quantum yield and favorable biocompatibility, and therefore are suitable for high-resolution in vivo imaging applications.